Design guideline for Si/organic hybrid solar cell with interdigitated back contact structure - Prakoso, Ari Bimo (2020)
We study the design of Si/organic hybrid (SOH) solar cells with interdigitated back contact (IBC) structure. SOH solar cells formed between n-Si and poly(3,4-ethylenedioxythiophene): polystyrenesulphonate (PEDOT:PSS) is a promising concept that combines the excellent electronic properties of Si with the solution-based processing advantage of an organic polymer. The IBC cell structure is employed to minimize parasitic absorption losses in the organic polymer, eliminate grid shadowing losses, and allow excellent passivation of the front Si surface in one step over a large area. The influence of Si thickness, doping concentration and contact geometry are simulated in this study to optimize the performance of the SOH-IBC solar cell. We found that a high power conversion efficiency of >20% can be achieved for optimized SOH-IBC cell based on a thin c-Si substrate of 40 μm thickness.